ANNUAL CYCLING PASSES BY FREE WRESTLING PERIODICAL RENEWAL OF THE TOOLS - Adiba O’razboyeva Abdug’aniyevna (Galaxy International Interdisciplinary Research Journal, 2024)
This article describes the use of recovery tools during the transition period of the annual cycle of freestyle wrestling.